DIGITAL BUSINESS-TO-BUSINESS MARKETING COMMUNICATIONS IN EMERGING MARKETS – Developing Business Marketing in Russia - Pyhämäki, Mika (My University, 2012)
The core idea of this Master's Thesis was that five key characteristics – market heterogeneity, sociopolitical governance, chronic shortage of resources, unbranded competition, and inadequate infrastructure – of emerging markets are radically different from the traditional industrialized capitalist society and they will require us to rethink the core assumptions of business-to-business marketing, such as business relationships, marketing communication elements, and digitalization. In this research, Russia is considered to be an emerging market that reflects the aforementioned theoretical characteristics. The research was a qualitative case study and furthermore a collective case study. In the beginning three digital marketing professionals were interviewed to better understand digital B2B marketing. The actual research data was collected through seven structured theme interviews with representatives of the case companies operating in Russia. The selection of case companies included three business consulting companies and four industrial companies. The aim of this qualitative study was to understand and clarify how business marketing exploits digital marketing methods as a part of the chosen business marketing strategy under emerging markets’ special conditions. This objective was divided in three research questions: 1) How the chosen marketing strategy reflects in the business marketing process? 2) How digital marketing communication contributes to business marketing? 3) How are the emerging markets’ characteristics reflected in the business marketing process? The main research findings indicate that digital business-to-business marketing communications can be useful and effective. Moreover, business DMC can be defined and structured in a reasonable way. The company's prevalent marketing paradigm and the chosen marketing strategy reflect in the business marketing process, and in utilizing digital marketing communications. The assumption that emerging markets set an environment with special characteristics for business marketing was supported by the study. However, the business environmental aspects were not considerably disturbing digital B2B marketing, but making it even more reasonable to harness in Russia.